Linking Employee Training And Development To Enhanced Customer Satisfaction In Hotels - Sandy, M. Yusuf (Journal of International Multidisciplinary Research, 2025)
This study aims to examine the relationship between employee training and development programs and customer satisfaction levels within the hospitality sector, with a particular focus on MaxOne Hotels in Makassar. Employing a mixed-methods approach, the research integrates employee surveys, customer feedback, and performance metric analysis to assess the influence of training programs on service quality and customer experiences. The findings reveal that employee training and development variables account for only 1.4% of the variance in customer satisfaction, with the remaining 98.6% influenced by other factors. Nevertheless, well-structured training program designs were shown to significantly enhance employees' critical thinking, communication, emotional regulation, and problem-solving skills. Furthermore, technology-based training demonstrates substantial potential for improving service efficiency and facilitating adaptation to operational innovations. In conclusion, while the direct impact of training on customer satisfaction is relatively minor, thoughtfully designed training programs remain essential for delivering high-quality customer experiences and sustaining competitiveness in the industry. This research offers valuable insights into strategies for optimizing training effectiveness in the hospitality sector.